Therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy : 10-year experience - Sequeira, Ana Teresa (2021)
© Author(s) (or their employer(s)) and Portuguese Journal of Pediatrics 2020. Re-use permitted under CC BY-NC. No commercial re-use